FILARIAL INFECTION BY APROCTELLA STODDARDI CRAM, 1931 (NEMATODA: ONCHOCERCIDAE) IN PASSERIFORMES FROM PERIURBAN AREAS, PARÁ STATE, BRAZIL - Rabelo, Adriane M. P. (2022)
Reports of filarial nematodes in wild birds are scarce in South America, particularly in the Amazon region. We analyzed the organs in the thoracic and abdominal cavities of 34 wild birds belonging to 12 different species of the order Passeriformes in the Periurban areas of Para State. Adult filariae was observed in 3/34 (9%) birds, located in the abdominal cavity of hosts. The morphological and morphometric characteristics of the filarial nematodes were consistent with the taxonomic classification of Aproctella stoddardi Cram, 1931, making this the first report of this species in the Amazon region in northern Brazil. Due to the observed migration of other genera of filariae, Aproctella Cram, 1931 may have the ability to infection at other sites, such as the liver, heart, lung, and brain. In addition, it is necessary to expand the records of the presence of filariae in birds of the region to elucidate the factors that influence this infection.